EVALUASI PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) MENGGUNAKAN METODE HIRARC PADA PROYEK PRESERVASI JALAN RIGID PAVEMENT BABAT-LAMONGAN-GRESIK - Maria Fransiska Trinity Juraman; Michella Beatrix (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Human resources play an important role for the success of an organization or company system. Because humans are living assets that need special attention by companies. The fact that humans are the main asset in an organization or company, must receive serious attention and be managed as well as possible. This is intended so that the human resources owned by the company are able to provide optimal contributions in efforts to achieve organizational goals. It is in the management of human resources that management is required to be able to manage resources in a systematic, planned and efficient manner. In human resource management, there is also one thing that must be a concern, namely, the occupational safety and health system. Occupational safety and health (K3) issues in general in Indonesia are often neglected. This is indicated by the still high number of work accidents. In Indonesia, especially in the business world that requires a large workforce such as construction projects, occupational health and safety is often ignored with the classic reason by business owners that the costs for occupational health and safety for workers are considered expensive. As is the case with PT. Cahya Indah, which is a company engaged in the construction sector with a large work capacity, it is fitting that the Occupational Health and Safety of workers be considered. Implementation of Occupational Safety and Health (K3) carried out by the construction sector. One example of construction sector activity is at PT. Beautiful Light. PT Cahya Indah is one of the companies in Indonesia engaged in construction. Where this company is engaged in the Rigid Pavement Road Preservation Project Tripe Lamongan Gresik. The road in this project has a long span of 16.5 km, located at stations 27 + 440 - 35 + 100 KM located on Jalan Raya Babat - Lamongan - Gresik, East Java. This study uses the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. HIRARC is a process of identifying hazards that can occur in both routine and non-routine activities, which is then carried out by an assessment process based on the identified hazards or risks to determine the high or low value of a risk so as to assist in the control process. In its preparation, HIRARC is divided into 3 stages including: hazard identification, risk assessment, and risk control